A Sensitive, Specific and Fast Electrochemical‐based Nanobiosensor Diagnostic for Xanthomonas albilineans, the Cause of Sugarcane Leaf Scald Disease - Moutoshi Chakraborty; Shamsul Arafin Bhuiyan; Simon Strachan; Muhammad J.A. Shiddiky; Nam‐Trung Nguyen; Narshone Soda; Rebecca Ford (Advanced Sensor Research)
Abstract Leaf scald (LS) caused by Xanthomonas albilineans (Xalb), is a major bacterial disease of sugarcane. The unreliable symptom expressions make traditional visual detection challenging. The molecular methods of detection require expensive equipment, labor‐intensive, and time‐consuming. This study proposes a novel electrochemical (EC)‐approach, that is relatively easy to use and less expensive to detect Xalb DNA in LS‐infected sugarcane leaves, meristematic tissue, and xylem sap samples. This method involves three key steps: i) DNA isolation from sugarcane samples via boiling lysis; ii) magnetic purification of target sequences from the lysate using magnetic bead‐bound capture probes; and iii) EC detection of the target DNA. The method shows excellent detection sensitivity (10 cells µL−1), reproducibility (Standard deviation, SD <5%, for n = 3), and a wide linear dynamic range (1 nM–1 fM or 106–10° copies µL−1, r = 0.99). The EC assay has a strong negative correlation with quantitative polymerase chain reaction (qPCR) results (r = −0.95–0.97, n = 24, p < 0.001), and weak or no correlation with the varietal resistance ratings. This EC‐based assay can be a commercially viable alternative, providing a DNA isolation/purification‐free solution, and can potentially be adapted into a handheld device for on‐farm detection and quantification of the LS‐causing pathogen.